Material design of two-phase-coexisting niobate dielectrics by electrostatic adsorption. (26th September 2017) - Fuchigami, Teruaki; Yoshida, Katsuya; Kakimoto, Ken-ichi
Abstract: A material design process using electrostatic adsorption was proposed to synthesize composite ceramics with a two-phase-coexisting structure. Supported particles were fabricated by the electrostatic adsorption of (Na, K)NbO3 –SrTiO3 (NKN–ST) nanoparticles on (Na, K)NbO3 –Ba2 NaNb5 O15 (NKN–BNN) particles. NKN–ST and NKN–BNN were well dispersed with no aggregate in NKN–ST/NKN–BNN ceramics synthesized using the supported particles in comparison with ceramics synthesized using a mixture obtained by simply mixing NKN–ST and NKN–BNN powder. The temperature dependence of dielectric constant is closely related to the composite structure and the dielectric constant was stable in a wide temperature range from room temperature to 400 °C. Capacitance for DC bias was also insensitive to temperature in the range of 0–2 kV/mm, and the change rate of the capacitance was within ±5% in the temperature range from room temperature to 200 °C.